The value of aqueous assessment in diagnosing dry eye - Ithnin, Mohd. Hafidz; Ariffin, Azrin Esmady; Mohd. Kamal, Khairidzan (Kulliyyah of Medicine, International Islamic University Malaysia, 2017)
Introduction: The clinical evaluation of the three layers of tear film is still poorly described. The purpose of this study is to evaluate the value of aqueous assessment in diagnosing dry eye.